PKM SOSIALISASI PENDIDIKAN PROFESI AKUNTAN DI SMK MUHAMMADIYAH 2 PEKANBARU - Oemar, Fahmi; Wardi, Jeni; Pili, Burhan; Indarti, Indarti; Al Ucok, Imran (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Accounting is the science of preparing financial statements and various accounting professions so that they can be prepared to continue their studies in the accounting department, while an accountant is a profession that practices accounting. The accounting profession is very diverse, ranging from public accountants, corporate accountants, educational accountants, to government accountants. Each type of accounting profession has different qualifications, duties, and responsibilities. For vocational high school students, knowledge about the accounting profession is still very limited, so there is a need for awareness-raising activities regarding this matter. This community service activity aims to provide a better understanding of the accounting profession. It is hoped that schools can guide their students in choosing an accounting major when continuing their studies at universities, particularly Lancang Kuning University. Therefore, this socialization of the accounting profession can be seen as an opportunity amid the challenges that will be faced in the future. The socialization was conducted in the form of lectures, question-and-answer sessions, and discussions over the course of one day, given the busy schedule of the students at SMK Muhammadiyah 2, Grade XII. The participants were highly enthusiastic about the material presented, as the presenter delivered it in a light-hearted manner tailored to the Gen Z audience of today. The participants were able to follow the material well and actively participated in the question-and-answer session. The final evaluation yielded positive responses and enthusiasm from the students of SMK Muhamadiyah 2 Pekanbaru and the teaching staff involved in the outreach program.